UTILIZATION OF SPENT BLEACHING EARTH WASTE ON LIME-SOIL STABILIZATION FOR ROAD BODY FOUNDATION LAYER BASED ON SOIL MECHANICAL - Zanjabil, Ananda Anggiat; Priadi, Eka; Bachtiar, Vivi (Fakultas Teknik Universitas Tanjungpura, 2023)
Soil stabilization is mixing soil with specific materials to improve the soil's technical attributes to meet specific technical requirements, such as increasing its stability. One stabilization method is chemical stabilization, which utilizes mixing heaped soil using lime and Spent Bleaching Earth (SBE). This research is focused on the effect of mixing lime with SBE for soil stabilization with maintenance time between 0, 7, and 14 days. The amount of lime used in the research is 4% from the soil dry weight with variations of the SBE mixture of 5%, 10%, 15%, and 20%. The conclusion obtained in this study was that adding SBE could increase the maximum dry density up to a percentage of 10%. Using SBE of more than 10% reduces the maximum dry density value but increases the optimum moisture content. From the mechanical attributes testing carried out, it can be seen that a percentage of 10% can increase the results of mechanical testing, while an increment above 10% will reduce the mechanical results. Based on the CBR and UCS test results, we found that lime and SBE mixture can pass the attributes limit for a grade S aggregate foundation layer and full-fill the requirement as a road body foundation layer. So, it can be concluded that lime and SBE mixture can be used as a road body foundation layer but has not reached the target for road foundation layers and requires maintenance for some time.